TAMAN SATWA KOTA PONTIANAK (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Animal Park is a form of ex-situ conservation institution that functions as a forum for preserving fauna outside of their natural habitat which is public. Besides having a conservation function, the Animal Park also has recreational, educational and research functions. Animal Park Planning in Pontianak City is also a form of designation and management of protected areas that are able to pay attention to the sustainability of supporting environmental functions in Pontianak City. This article aims to explain the process of designing a Wildlife Park as a recreation and tourism center regarding the introduction of native animals of West Kalimantan. The theme or design concept that is planned is the consideration of the animal's life behavior without reducing the comfort from the visitor's side. This design provides a boundary between the end zone and the animal zone, as well as the placement of a management service zone that is separate from the visitor zone but can still be connected to each animal enclosure. In the design carried out, the enclosure for the animal habitat uses a membrane structure for primate species and a wide-span structure to form an aviary enclosure for aves species.